2019
DOI: 10.1159/000496791
|View full text |Cite
|
Sign up to set email alerts
|

Urinary and Fecal Continence in 5-Year-Old Patients Who Underwent in utero Myelomeningocele Repair: A Prospective Study

Abstract: <b><i>Introduction:</i></b> After<b><i></i></b> the successful results of in utero myelomeningocele (MMC) repair presented by the Management of Myelomeningocele Study, the concept of fetal surgery was introduced in our institution in 2011. Since then, we have been able to follow prospectively a group of patients with attention to urological care. In the present study, we were interested in estimating urinary and fecal continence in this new subset of patients. &l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Patients may suffer from either fecal incontinence or constipation. One small study of fourteen patients who underwent prenatal MMC repair found that almost 80% continued to require diaper use by age five due to fecal incontinence [ 27 ]. A large proportion of patients require complex bowel regimens, including retrograde rectal irrigations (57%) or medications such as oral laxatives (79%) [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients may suffer from either fecal incontinence or constipation. One small study of fourteen patients who underwent prenatal MMC repair found that almost 80% continued to require diaper use by age five due to fecal incontinence [ 27 ]. A large proportion of patients require complex bowel regimens, including retrograde rectal irrigations (57%) or medications such as oral laxatives (79%) [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…One small study of fourteen patients who underwent prenatal MMC repair found that almost 80% continued to require diaper use by age five due to fecal incontinence [ 27 ]. A large proportion of patients require complex bowel regimens, including retrograde rectal irrigations (57%) or medications such as oral laxatives (79%) [ 27 ]. In another long-term follow up of children with prenatally repaired MMC, only 26% reported continence all the time, and almost 60% were enrolled in a bowel management program at a median age of 10 years old [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, several studies suggested little benefit of prenatal OSB repair concerning the urinary tract. The group of Macedo published several studies [12, 14, 15, 28, 29] of prospectively followed up patients with prenatal OSB repair and a high incidence of abnormal bladder patterns. In an analysis of 100 patients [15], only 15% showed a normal bladder profile at a mean age of 5.8 months (median 4 months).…”
Section: Discussionmentioning
confidence: 99%
“…The potential improvement in the bladder function is a controversial subject, as the different studies published in the post-MOMS era are conflicting. When analyzing prospective studies, the American groups involved in MOMS (2,3) and the Zurich group (4,5) suggest benefits of in utero MMC to the bladder function, while our studies in São Paulo go in the opposite direction and shows no improvements to bladder function, regardless if MMC closure had been in utero or postnatal (6)(7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 63%